Prevalence, clinical manifestations, and biochemical data of type 2 diabetes mellitus versus nondiabetic symptomatic patients with COVID-19: A comparative study - Soliman, Ashraf T; Prabhakaran Nair, Arun; Al Masalamani , Muna S.; De Sanctis, Vincenzo; Abu Khattab , Mohamad A.; Alsaud, Arwa E.; Sasi, Sreethish; Ali, Elrazi A.; Ola A., Hassan; Iqbal, Fatima M.; Nashwan, Abdulqadir J.; Fahad, Jesin; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background: There is a scarcity of data regarding the effect of Type 2 diabetes mellitus (T2DM) and associated comorbidities on the clinical presentation and outcome of symptomatic patients with -COVID-19 infection in comparison with non-diabetic patients. Aim of the study: We described and compared the clinical presentation and radiological and hematological data of a cohort of symptomatic COVID19 positive T2DM diabetic patients (n = 59) versus another cohort of non-diabetic symptomatic COVID19 positive patients (n =244) diagnosed at the same time from January 2020 to May 2020. Associated comorbidities were -assessed, and the Charlson Comorbidity Index was calculated. The outcomes including duration of hospitalization, duration of Intensive Care Unit (ICU) stay, duration of mechanical ventilation, and duration of O2 -supplementation were assessed. Results: Prevalence of T2DM in symptomatic COVID19 positive patients was 59/303 (=19.5%).  Diabetic patients had higher prevalence of hypertension, chronic kidney disease (CKD) and cardiac dysfunction [coronary heart disease (CHD)], and congestive heart failure (CHF). Charlson Comorbidity score was significantly higher in the T2DM patients (2.4± 1.6) versus the non-diabetic -patients (0.28 ± 0.8; p: < 0.001). Clinically and radiologically, T2DM patients had significantly higher percentage of pneumonia, severe pneumonia and ARDS versus the non-diabetic patients. Hematologically, diabetic patients had significantly higher C-reactive protein (CRP), higher absolute neutrophilic count (ANC) and lower counts of lymphocytes and eosinophils compared to non-diabetic patients. They had significantly higher systolic and diastolic blood pressures, longer duration of hospitalization, ICU stay, mechanical ventilation and oxygen therapy. CRP was correlated significantly with the duration of stay in the ICU and the duration for oxygen supplementation (r = 0.37 and 0.42 respectively; p: